ASSISTIVE TECHNOLOGIES IN INTERDISCIPLINARY SPECIAL EDUCATION: A REVIEW OF CURRENT PRACTICES - Soni, Chandrika; Singh, Preeti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper provides a comprehensive review of the current practices utilizing assistive technologies in enhancing collaboration with interdisciplinary special education. Based on the review of identified secondary sources, it explores the significance of assistive technologies in supporting diverse learners with disabilities by examining the current practices utilizing assistive technologies and assesses their effectiveness in promoting inclusive education. Additionally, it highlights the collaborative nature of interdisciplinary special education and how assistive technologies can enhance the collaboration among educators, therapists, and specialists to improve the learning outcomes of students with disabilities. By examining the existing practices, evaluating their effectiveness, and identifying and addressing challenges, this paper contributes to the ongoing dialogue on improving the quality of education for individuals with special needs. The paper concludes that the current practices not only enhance the educational experiences of students with disabilities but also contribute to their improved learning outcomes, increased engagement, and overall inclusion in general education settings. By recognizing and overcoming the identified challenges, interdisciplinary special education can harness the full potential of assistive technologies to enhance collaboration and further improve the learning outcomes of students with disabilities.